Pengaruh Kualitas Pelayanan dan Harga terhadap Kepuasan Konsumen pada Bengkel Servis: (Studi Pada PT. AHASS di Kabupaten dan Kota X) - Ary Kusmanto (Jurnal Bisnis Kreatif dan Inovatif, 2025)
Population growth in Indonesia increases the need for transportation, especially motorbikes, which makes the vehicle market more competitive and provides consumers with many choices. Consumers choose motorbikes based on price, after-sales service, quality, fuel efficiency and quality of workshop service. Good workshop service with easy administration and original spare parts will make consumers satisfied, while bad service will make them dissatisfied. Service quality is measured by the provider's ability to meet customer expectations, which influences customer satisfaction. Satisfaction is achieved when the results received are in line with expectations, including product quality, price and after-sales service. With the number of Honda motorbikes increasing and the number of AHASS workshops, competition is getting tougher, forcing organizations to provide high-quality services to attract new customers. The research method used was quantitative with a sample size of 291 customer respondents from the PT service workshop. AHASS. The research results show that service quality and price have a positive and significant effect on consumer satisfaction.